Factors Associated with Hypertension among Urban Dwellers with Sedentary Lifestyle: A Cross-Sectional Study - Joardar, Ariful Islam; Khaled, Md Fakhrul Islam; Mahabub, SM Eare; Singha, Chayan Kumar; Haque, M Atiqul (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Hypertension is a serious public health problem and an important research area due to its worldwide high prevalence and being a prime risk factor for cardiovascular diseases and other complications. In developing countries, hypertension is more prevalent among the urban population who lead a sedentary lifestyle. Objective:This study aimed to investigate the prevalence and risk factors of hypertension among urban dwellers with sedentary life. Methodology: This cross-sectional study was conducted among the adult population (18 years and above) living in one of the urban areas of Dhaka (Dania Union, Kadamtali Thana), Bangladesh. The study was conducted from January 2018 to October 2018, using a simple random sampling technique for data collection. The adult respondents were enrolled in this study who were staying at home and leading a sedentary lifestyle. Univariate analysis and binary logistic regression analysis were performed to examine the risk factors of hypertension of the study population. Results: A total of 149 adults were enrolled in this study. The mean (±SD) age of the study population was 51.20 (±14.65) years. About four out of 10 study population were found to be hypertensive in this study. The adjusted logistic regression analysis revealed that increased age groups, i.e., 50 to 60 years old [AOR: 3.11, 95% CI: 1.01 – 9.66] and 60 years old and above [AOR: 5.83, 95% CI: 1.73 – 20.06], and family history of hypertension (AOR: 3.59, 95% CI: 1.34 - 9.63) had a positive and significant association with hypertension. However, people with high socioeconomic status showed 71 percent less likelihood of being hypertensive than the lower ones. Conclusion: The prevalence of hypertension among the people leading a sedentary lifestyle was significantly higher in this study. Increasing physical activity, maintaining proper antihypertensive medication, and regular follow-up of hypertension for older adults might inhibit the increased prevalence of hypertension in urban areas. Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 129-134